“Educare all'Antico”. Teaching Classical Civilisation in Italian primary and lower secondary schools - Di Donato, Riccardo; Taddei, Andrea (Journal of Classics Teaching, 2024)
The purpose of this article is to offer an overview of an educational project that brought Classical Civilisation to pupils in the Pisa area between 2004 and 2009, through a cooperation between the Department of Classical Philology at our University and the Provincial Administration of Pisa.1 The project was aimed at pupils of primary and lower secondary schools, in response to a thorough reform of the Italian school system that excluded some pupils from studying Greek and Roman civilisations in as much depth as other parts of history. This article will first provide an overview of the Italian education system and its recent reforms, after which the project Educare all'Antico will be discussed.